Factors Causing Learning Difficulties in Elementary School Students' Understanding of Optical Concepts - Anggi Harnum Lestari Nasution; Dwina Nurmalia Putri; Shofa Shofiyana; Yugnita Azmi Awalliyah; Afridha Laily Alindra (BIOCHEPHY: Journal of Science Education, 2026)
Natural Science learning in elementary schools plays a crucial role in building students' scientific thinking skills. However, understanding basic optical concepts such as light, reflection, refraction, propagation, and shadow formation remains a significant challenge. This study aims to analyse the factors causing students' learning difficulties in understanding basic optical concepts through a literature review. The method employed was a review of eight scientific articles published between 2020 and 2026, sourced from Google Scholar and SINTA, using content analysis techniques. The findings show that students still experience misconceptions in optical concepts, particularly in reflection, refraction, and light dispersion. Learning difficulties are influenced by internal factors such as low prior understanding, limited abstract thinking ability, and learning motivation as well as external factors, including the dominance of lecture-based methods, insufficient learning media, limited practicum activities, and suboptimal use of diagnostic instruments. Efforts to address these difficulties can be pursued through conceptual change strategies, the Predict-Observe-Explain (POE) model, multiple representations, and the use of virtual laboratories to help students visualise abstract concepts in a more concrete and meaningful way.